Opportunistic Change During a Punctuation: How and When the Front Lines Can Drive Bursts of Incremental Change - Yang, Elisabeth; DiBenigno, Julia (Organization Science, 2025)
Environmental jolts can trigger more conducive conditions for driving change in organizations. However, punctuated equilibrium theories of organizational change concentrate on top managers’ implementation of de novo radical changes after jolts. Existing research has not examined frontline-driven, incremental change efforts during these periods of disrupted stasis, despite the value of frontline change ideas. We develop a process model to explain how and when those on an organization’s front lines can leverage a jolt to opportunistically implement long-desired change ideas in ways that promote their retention. We conducted a two-year qualitative field study at a hospital during the Covid-19 pandemic, examining the trajectories of 33 premeditated change ideas raised by frontline staff. By comparing ideas that persisted to become part of normal operations with those that failed to be selected or retained, we identified practices and conditions that promoted the selection and retention of frontline change ideas. Our study suggests that frontline change advocates can seed the long-term retention of “shovel-ready” ideas—as opposed to de novo ideas—after a jolt by rapidly and opportunistically deploying a novel set of practices before the brief window of opportunity created by lessened constraints and increased managerial receptivity closes. Prior theories of change largely assume frontline-driven change to be slow and continuous, proceeding in a one-off fashion; we explain how and when frontline change can instead occur in rapid, opportunistic bursts. This study advances theories of punctuated equilibrium and bottom-up change in organizations by unearthing an alternative way that change can be intentionally accomplished in organizations. Supplemental Material: The online appendix is available at https://doi.org/10.1287/orsc.2021.15120 .